Risk factors for HIV seropositivity among people consulting for HIV antibody testing: a pilot surveillance study in Quebec. - Alary, M (1990)
The surveillance of AIDS (acquired immune deficiency syndrome) through case reporting only reflects the epidemiologic features of HIV (human immunodeficiency virus) transmission a few years earlier and not the prevalence of HIV seropositivity. HIV infection is not a notifiable condition in Quebec. We were asked by the ministère de la Santé et des Services sociaux du Québec to perform a pilot project for the surveillance of HIV seropositivity using a network of sentinel physicians. From May 15, 1988, to Sept. 30, 1989, physicians from four collaborating centres collected data on the serologic status, demographic characteristics and risk factors for 4209 patients who underwent HIV antibody testing. Of the 3899 subjects included in the study 7.9% were HIV positive. Through logistic regression analysis the following variables were found to be significantly associated with HIV seropositivity: presence of HIV-related symptoms (prevalence odds ratio [POR] 36.5), origin from an endemic area (POR 9.1), homosexuality or bisexuality (POR 8.4), intravenous drug use (POR 4.2), male sex (POR 2.8), previous HIV antibody testing (POR 2.5) and previous sexually transmitted disease (POR 1.8). Over the study period we found a large increase in HIV seroprevalence among intravenous drug users (4.2% in 1988 to 19.0% in 1989) (p = 0.02). This increase might reflect a recent change in the epidemiologic pattern of HIV transmission in Quebec. Surveillance of HIV seropositivity through a network of sentinel physicians may be a reasonable alternative to mandatory reporting.